Konstruksi Makna Budaya Jawa melalui Tanda Visual dalam Game A Space for the Unbound - Asyraf Rafiq; Chelsy Yesicha (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. This study examines the representation of Javanese culture in A Space for the Unbound, a game developed by Mojiken Studio, as a form of local identity negotiation within the globalization of the video game industry. In the era of global popular culture, local games can function as strategic spaces for affirming cultural identity. This research aims to analyze the meanings of Javanese cultural symbols such as traditional architecture, surjan attire and blangkon, traditional music arts, and social practices of the 1990s through Roland Barthes’ semiotic approach, which encompasses three layers of meaning: denotation, connotation, and myth. A descriptive qualitative method employing visual and textual observation was used for data collection. The findings indicate that at the level of denotation, the symbols are presented literally in accordance with Javanese social reality. At the connotative level, these symbols evoke collective social and emotional meanings, including nostalgia, solidarity, and the spirit of gotong royong (mutual cooperation). At the mythic level, the game constructs a narrative of Javanese culture as an ancestral heritage imbued with moral, spiritual, and social values. Therefore, A Space for the Unbound effectively functions as a medium of cultural representation that reinforces local identity awareness amid global modernization. Abstrak. Artikel ini mengkaji representasi budaya Jawa dalam GameA Space for the Unbound karya Mojiken Studio sebagai wujud negosiasi identitas lokal di tengah globalisasi industri video game. Dalam era budaya populer global, game lokal dapat menjadi ruang strategis untuk meneguhkan identitas kultural. Penelitian ini bertujuan menganalisis makna simbol budaya Jawa pada arsitektur tradisional, pakaian adat Surjan dan blangkon, seni musik tradisional, dan praktik sosial pada tahun 1990an melalui pendekatan semiotika Roland Barthes pada tiga lapisan makna: denotasi, konotasi, dan mitos. Hasil temuan menunjukkan bahwa pada level denotasi, simbol ditampilkan secara literal sesuai realitas sosial Jawa. Level konotasi memunculkan simbol makna sosial dan emosional kolektif, seperti nostalgia, solidaritas, dan semangat gotong royong. Sedangkan pada level mitos memperlihatkan penyajian narasi budaya Jawa adalah warisan leluhur yang mengukuhkan nilai moral, spiritual, dan sosial. Hal ini membuktikan A Space for the Unbound berperan sebagai media representasi budaya yang memperkuat kesadaran identitas lokal dalam modernisasi global khususnya budaya Jawa.